Long-term results of facial animation surgery in patients with Moebius syndrome. Issue 12 (December 2020) - Bianchi, Bernardo; Zito, Francesca; Perlangeli, Giuseppe; Pedrazzi, Giuseppe; Ferrari, Pier Francesco; De Stefani, Elisa; Sesenna, Enrico; Di Tano, Andrea; Ferri, Andrea
Abstract: Gracilis neuromuscular transplant is considered the gold standard for facial animation in Moebius syndrome patients. However, long-term evaluation of the results has not been critically examined in the international literature. Thus, it remains unknown how the transplanted flap changes with facial growth, and whether contraction (smiling) is maintained. Pediatric patients with Moebius syndrome who underwent facial animation surgery with at least 5 years of follow-up were retrospectively examined. Photographs taken at the 1-year and most recent follow-up visits were analyzed and compared using Emotrics software. Analyses focused on the rest position, and on gentle and maximum smiles. Eighteen patients were enrolled. Seven patients had bilateral and 11 unilateral Moebius syndrome; therefore, 25 gracilis transplants were analyzed. The latest follow-ups ranged from 5 to 13.2 years (mean 7.6 years). The three principal facial expressions that were examined did not differ significantly between 1 year and a mean of 7.6 years after surgery, but tended to improve in most patients. Commissure excursion and smile angle for the maximum smile did improve significantly ( p = 0.002 and 0.029, respectively). The series examined in this study supports the limited literature regarding the long-term stability of gracilis transplantation to animate the faces of Moebius syndrome children.